Effects of astaxanthin on biochemical and histopathological parameters related to oxidative stress on testes of rats on high fructose regime. (9th May 2018) - Dokumacioglu, E.; Iskender, H.; Yenice, G.; Kapakin, K. A. T.; Sevim, C.; Hayirli, A.; Saral, S.; Comakli, S.
Summary: Astaxanthin (ASX) is a xanthophyll family of hydroxycarotenoids which contains several double bonds. It is produced by Haemococcus pluvialis, a microalgae and possesses antioxidant and anti‐inflammatory properties. The aim of this study was to test whether ASX could protect against oxidative damage in the testicular tissues of rats receiving high fructose. The rats ( n  = 24) were randomly divided into two main groups: control and fructose (30%, via drinking water) and then each main group either not supplemented or supplemented with ASX (1 mg kg −1 day −1, within 0.2 ml olive oil) via oral gavage. Data were subjected to two‐way ANOVA. High fructose consumption tended to increase testis weight and serum testosterone concentration and decreased testicular tissue glutathione‐ S ‐transferase (GST) and superoxide dismutase (SOD) levels, but did not affect testicular tissue malondialdehyde (MDA) concentration. Astaxanthin administration increased testosterone, GST and SOD levels and testis weight and decreased MDA concentration. However, ASX administration did not reverse alterations in antioxidant parameters caused by high fructose consumption. Inducible nitric oxide synthase (iNOS) tended to increase in sertoli cell, spermatid and spermatogonia, but not in spermatocytes and leydig cell in response to high fructose consumption. Astaxanthin administration tended to reverse elevation in iNOS in testis cells. In conclusion, ASX could help alleviate oxidative damage caused by high fructose consumption.